Cairo evaluation clinic: Thoughts on randomized trials for evaluation of development - Dean Karlan (Yale University, Economic Growth Center, 2009)
We were asked to discuss specific methodological approaches to evaluating three hypothetical interventions. This article uses this forum to discuss three misperceptions about randomized trials. First, nobody argues that randomized trials are appropriate in all settings, and for all questions. Everyone agrees that asking the right question is the highest priority. Second, the decision about what to measure and how to measure it, i.e., through qualitative or participatory methods versus quantitative survey or administrative data methods, is independent of the decision about whether to conduct a randomized trial. Third, randomized trials can be used to evaluate complex and dynamic processes, not just simple and static interventions. Evaluators should aim to answer the most important questions for future decisions, and to do so as reliably as possible. Reliability is improved with randomized trials, when feasible, and with attention to underlying theory and tests of why interventions work or fail so that lessons can be transferred as best as possible to other settings.
Keywords: B41; O12; H43; J08; H54; D73; D12; 330; program evaluation; randomized control trial